Differentiation of protein species of alpha-2u-globulin according to database entries: A half-theoretical approach - Aksu, Sevil; Tanrikulu, Fatmagül (Journal of proteomics, 2016)
The alpha-2u-globulin protein, the main subject of this study, is the most abundant protein in adult male rat urine. In this investigation there are 19 spots identified as alpha-2u-globulin by 2-DE and MALDI-TOF/TOF-MS. All of them are in the low molecular weight region, at approximately 15–25kDa. Searches within both, SwissProt and NCBI databases gave different from each other, but on the majority the same database entry as the highest ranked result for all spots. For this half-theoretical approach all entries from the NCBI database for the protein alpha-2u-globulin were considered in more detail. The sequences and the masses of the theoretically resulting tryptic peptides were compared with the PMF spectra of the spots identified as alpha-2u-globulin. This study presents a trial to distinguish between different protein species of that protein, only on the amino acid level. Other modifications like phosphorylation, glycosylation or any other group modification could not be considered here. Different protein species can be predicted for groups of closer positioned spots. Statements about which spot contains which peptide variant can be done, too. But it was found that several spots contain more than one protein species. In this investigation a half-theoretically approach was shown to differentiate between protein species of different spots identified as the same protein. Different positions of spots in 2-DE gels mean different contents of protein species. Here, peptide masses from sequences of protein database entries were searched in the PMF spectra of alpha-2u-globulin. Different peptide variants could be assigned to different spots. It was also found that several spots contain more than one peptide variant and therefore more than one protein species. In addition, the insufficiency of the database has been demonstrated. PMF spectra of 19 spots identified as alpha-2u-globulin. [Display omitted] •19 spots were identified as the alpha-2u-globulin protein in Wistar type male rat urine.•PMF spectra of different spots contain different peptide masses which belong to different peptide variants.•PMF spectra of some spots contain more than one mass for the same peptide, which means that some spots contain more than one protein species.